Epidemia do HIV e os determinantes sociais em saúde entre jovens no contexto amazônico: análise geograficamente ponderada e projeções temporais - PEDROSO, Andrey Oeiras (Universidade Federal do Pará, 2023)
Introduction: In Brazil, the HIV/AIDS detection rate (/100,000 inhab.) showed a decrease in the general population of 17.2%, from 2009 (21.5) to 2019 (17.8). However, this rate increased substantially among the young population, which had the highest detection rate in the country, 52.0 (/100,000 inhab.) (BRASIL, 2020a). This advance on the young population is due to obstructions, discrimination, inequalities, stigmas and social and health inequities, intrinsic vulnerabilities of this population stratum that enhance their chances of becoming infected with HIV. However, the risk of HIV infection cannot be conditioned only to the individual, since behaviors are directly influenced by socioeconomic territorial factors that exceed the individual. Despite all the advancement of HIV among young people, there is a scarcity of studies aimed at analyzing the impact of Social Determinants of Health (SDH) on the epidemic in this age group. Objective: To analyze temporally and spatially the HIV epidemic among young people in the State of Pará. Methods: An ecological study that analyzed HIV/AIDS cases diagnosed between 2007 and 2018 in Pará, Brazil. An exploratory analysis was performed using descriptive statistics. The temporal projections (2019-2022) used mixed method, ARIMA + STL in the RStudio software. For the spatial analysis, we used statistical scanning techniques to obtain the Relative Risk (RR), with a confidence interval of 95%; Moran's autocorrelation statistic considering statistically significant (p < 0.05) for building the LISAMap in ArcGIS software. In SPSS software, we developed models from Ordinary Least Squares (OLS) and later by Geographically Weighted Regression (GWR), with spatial analysis of residuals, with the help of MGWR and ArcGIS software. Results: Of the 8,143 cases analyzed, 47.97% were young people between 25 and 29 years old, men (66.46%), mixed race (76.95%), living in urban areas (85.20%) and heterosexuals (54 .41%). An expansion of HIV among young people in Pará was identified, with a temporal projection of increase for young people aged 20-24 years. Spatial variability of DSS: 'Basic Education Development Index'; doctors per 10,000 inhabitants and municipal high school abandonment (MHSA) rate were associated with the risk of HIV infection among young people. The relative risk showed spatial variability. Conclusions: The SDH associated with HIV risk among young people in Pará, show social particularities of HIV in the study region and should be considered in the formulation of policies to reach the global goal of eliminating AIDS by 2030 among young people.